Novel properties of vacancy-ordered perovskite-Cs2BCl6 induced by d-orbital electrons - Siyu Zhang; Lu Wang; Yujia Guo; Jie Su; Haidong Yuan; Zhenhua Lin; Lixin Guo; Yue Hao; Jingjing Chang (Journal of Materiomics)
The all-inorganic lead-free vacancy-ordered perovskite offers a promising avenue toward nontoxic and stable optoelectronic materials. Herein, we present a first-principles study of the structural stability, optical absorption, electronic structure, and mechanical behavior of Cs2BCl6 compounds with B-site substitutions (BGe, Sn, Pb, Cr, Mo, W, Ti, Zr, and Hf). The structural analysis shows that the Cs2BCl6 perovskite with face-centered cubes has a stable chemical environment, especially Cs2HfCl6, Cs2WCl6, and Cs2PbCl6. Hf4+ and W4+ with high-energy d-state external electron configurations can further lower the valence band maximum position of the Cs2BCl6 structures and thus increase the band gap, assisting in tuning the optical absorption and emission properties of these structures in the optoelectronic application. For the light absorption properties of Cs2BCl6 materials, the best light absorption properties have been concluded for Ti4+, Cr4+, and Pb4+-based perovskite in the visible range due to a suitable band gap. Therefore, the excellent optical absorption and electronic properties make these vacancy-ordered perovskites promising candidates for optoelectronic applications.